O Homen e a Galinha, de Ruth Rocha, na perspectiva da semiótica do texto - Köche, Vanilda Salton; Pavani, Cinara Ferreira (Signo, 2019)
O Homen e a Galinha, de Ruth Rocha, na perspectiva da semiótica do texto